2019
DOI: 10.4142/jvs.2019.20.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification of astroviruses in wild boars

Abstract: Astroviruses are widely detected in pigs but their detection in wild boars is rather sporadic. In this study, astroviruses were detected in organ homogenates of wild boars by applying nested reverse transcriptase polymerase chain reaction, and the typing was carried out by phylogenetic analysis. Overall, 30/200 (15.0%) homogenates were positive for astroviruses. Genetic typing revealed that of 13 amplicons analyzed, 8 were typed as porcine astrovirus lineage 2 (PAstV-2), 2 as lineage 4 (PAstV-4), 2 identical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Previous studies on AstVs in farmed and companion animals have demonstrated that turkeys, ducks, chickens, guinea fowl, pigeons, geese, mink, sheep, cattle, pigs, and cats are hosts of astroviruses [ 3 , 16 , 17 ]. In the population of wild animals, AstVs were mostly detected in bat samples, with several studies performed in wild boars in Slovakia and Hungary [ 29 , 30 ]. Metagenomics studies performed on rodents in China and red foxes in the Netherlands revealed novel rodent and fox astroviruses, respectively [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on AstVs in farmed and companion animals have demonstrated that turkeys, ducks, chickens, guinea fowl, pigeons, geese, mink, sheep, cattle, pigs, and cats are hosts of astroviruses [ 3 , 16 , 17 ]. In the population of wild animals, AstVs were mostly detected in bat samples, with several studies performed in wild boars in Slovakia and Hungary [ 29 , 30 ]. Metagenomics studies performed on rodents in China and red foxes in the Netherlands revealed novel rodent and fox astroviruses, respectively [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomics studies performed on rodents in China and red foxes in the Netherlands revealed novel rodent and fox astroviruses, respectively [ 31 , 32 ]. In our study, we screened a broad range of animal species using the method Chu et al [ 19 ] successfully applied for the detection of astroviruses in bats in Poland [ 18 ], in wild boars in Slovakia [ 29 ], and in different wild animals in Italy [ 33 ]. Although astroviruses were most frequently detected in rat samples, with a prevalence of 33.3%, the number of samples tested was only nine due to the low number of rat samples submitted during rabies surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrovirus wild boar WBAstV-1 8 11 Associated with gastroenteritis. Can be found in boars worldwide (Vilcek et al, 2019).…”
Section: Prrsv Genome Coveragementioning
confidence: 99%
“…The PAstV isolated from wild boars has previously reported in several countries including Hungary [32], Slovakia [33], and Korea [20]. Especially, PAstVs isolated in Slovakia have been typed genetic variable lineages involved in PAstV-2, PAstV-4, and AstVs derived from different species (Chicken and bat) [33]. Whereas, Korean wild boar PAstV isolated in 2013 was limited in strain typed into PAstV-4 lineage [20].…”
Section: Introductionmentioning
confidence: 99%